(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Cutaneous leishmaniasis in various endemic regions has its own specifics due to the uniqueness of environmental factors. Clinical observations of patients made it possible to generalize some characteristic clinical course of cutaneous leishmaniasis in endemic regions.